TRAINING ON THE DEVELOPMENT OF RESEARCH CENTRE AT SMAN 3 SEMARANG - Setyo Budi; Indra Gamayanto; Budi Widjajanto; Suharnawi; Achmad Wahid Kurniawan (Jurnal Layanan Masyarakat (Journal of Public Services), 2023)
Research is not only based on what we create, but whether the research can be applied and have a positive impact on society in general or not. SMAN 3 is one of the favorite schools in Semarang, but until a long time SMAN 3 Semarang has not been a research-based school, so this PkM aims to provide a more detailed understanding of research. The method used is by mentoring SMAN 3 Semarang in the process of becoming a research-based school, and building a journal as a medium to publish the results of student and teacher research. The result of this service was the establishment of a research centre at SMAN 3 Semarang and the journal Journey. With this journal, the published research results will be able to bring significant changes to sustainable research, where young people will be able to improve their competence in the field of research and can become reliable researchers in facing the era of globalization. Furthermore, in this community service, the step to build a smart centre is to apply it to the curriculum and this will be able to have a significant impact such as the establishment of UMKM to support the community's economy.